2017
DOI: 10.1002/lt.24827
|View full text |Cite
|
Sign up to set email alerts
|

Combined resistance and endurance training at a moderate‐to‐high intensity improves physical condition and quality of life in liver transplant patients

Abstract: Although currently moderate and high intensity concurrent physical exercise is prescribed in populations with special needs due to its greater effect on physical condition and health-related quality of life (HRQOL), there are no data in the liver transplantation (LT) setting. The aim of this study is to evaluate changes in maximal strength, aerobic capacity, body composition, liver function, and HRQOL in LT patients after a moderate-to-high intensity combined resistance-endurance training. Six months after LT,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
61
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 39 publications
(79 reference statements)
2
61
1
Order By: Relevance
“…To date, seven studies (four RCTs; three observational studies) have investigated the use of exercise after liver transplantation (Table ) in a total of five patient cohorts (n = 243), as two European populations were utilised twice . Participant numbers ranged from 15 to 119, with the latter being an American RCT from 2006 in which 41% received the exercise intervention; whilst the mean age was 39‐61 years with no gender predominance.…”
Section: Adherence To Exercisementioning
confidence: 99%
See 4 more Smart Citations
“…To date, seven studies (four RCTs; three observational studies) have investigated the use of exercise after liver transplantation (Table ) in a total of five patient cohorts (n = 243), as two European populations were utilised twice . Participant numbers ranged from 15 to 119, with the latter being an American RCT from 2006 in which 41% received the exercise intervention; whilst the mean age was 39‐61 years with no gender predominance.…”
Section: Adherence To Exercisementioning
confidence: 99%
“…Time spent exercising per week ranged from 90‐150 minutes with each session lasting between 30 and 75 minutes. Participants were instructed to complete their aerobic exercise sessions at either a moderate (60% heart rate reserve) or high (70%‐85% heart rate reserve) level of intensity, while Beyer et al reported that the intensity of the session was “individualised according to the patient's work capacity”.…”
Section: Adherence To Exercisementioning
confidence: 99%
See 3 more Smart Citations